Temporal trends in outpatient management of incident pulmonary embolism and associated mortality. Issue 161 (January 2018) - Klil-Drori, Adi J.; Coulombe, Janie; Suissa, Samy; Hirsch, Andrew; Tagalakis, Vicky
Abstract: Introduction: In clinical trial settings, outpatient management of pulmonary embolism (PE) is feasible and safe, but less is known on its use in routine care. We determined trends in outpatient management of PE and associated mortality in a large non-select patient population. Methods: All residents of Quebec, Canada with a first-ever work-up for suspected PE in the emergency department (ED) over 10 years were included. Patients could transition to outpatient management and from unconfirmed to confirmed PE in a time-varying fashion. Comparing the years 2005–9 with 2000–4, we assessed the odds ratio (OR) for outpatient management, and relative risk (RR) for all-cause mortality, readmissions for PE, and major bleeding in 30 days. We adjusted the RR for a mortality risk score. Results: Of 15, 217 patients included, 7583 were outpatients (7.5% confirmed PE) and 7634 were inpatients (60.6% confirmed PE). In all, 10.9% of patients with confirmed PE were outpatients, but outpatient management of confirmed PE was more likely in the latter study period (OR 1.73, 95%CI 1.44–2.09). Among outpatients with confirmed PE, mortality (RR 0.84, 95%CI 0.15–4.61) and readmission (RR 1.25, 95%CI 0.45–3.48) rates were stable, and only 3 major bleeding events were noted. Inpatients with confirmed PE had stable mortality rates (RR 0.95, 95%CI 0.72–1.24). Conclusion: Outpatient PE management increased over 10 years while remaining fairly uncommon. Nevertheless, stable mortality and readmission rates indicate this practice is safe in routine care, and add to the growing evidence in support of outpatient PE management. Highlights: More patients with confirmed PE were managed as outpatients over 10 years. Outpatients with confirmed PE had unchanged mortality. Readmission rates for outpatients with confirmed PE were stable. Major bleeding rates among outpatients were very low.